Contruction of the Meaning of the Song Imagine Jhon Lennon’s as a Media for Social Critism Communication for John Lennon Fans - Andriani, Astri Dwi; Sadikin, Dera Maharani (International Journal of Law Analytics, 2024)
This research is entitled "Construction of Song MeaningImagine John Lennon's work as a Social Criticism Communication Media for John Lennon Fans at Putra Indonesia University, Cianjur". The objectives of this research include how to construct the meaning of songsImagine John Lennon's work in the semiotics of Roland Barthes and how social criticism forms in songsImagine. The theory used in this research is Roland Barthes' semiotic theory. This research uses qualitative research methods with a semiotic approach. The data collection methods used in this research include observation, interviews, documentation, literature study, online data, and data triangulation. The results of this research show that from a denotative level analysis, songsImagine tells the story of John Lennon's anxiety about what happened in the world in 1971 when the conflict between Vietnam and America occurred. Then, in the connotative level analysis, songsImagine are John Lennon's dreams for the world and wrap his idealism into the song. In the analysis at the myth level, there is an ideology that is very often mentioned by John Lennon, namely "peace". John Lennon imagined several things in these lyrics which aimed to achieve a life full of peace without conflict.